Heavy episodic alcohol drinking among students from a rural South African university: Correlates with personal-social variables. Issue 4 (31st August 2016) - Nkoana, Shai; Sodi, Tholene; Darikwa, Timotheus B.
Abstract : The aim of the study was to explore the personal and social factors contributing to heavy episodic alcohol drinking (HEAD) in a sample of students from a rural South African university. A sample of 837 undergraduate students (females = 56.6%; age range of 17 to 43 years) participated in the study. Data on their use of alcohol were gathered using the AUDIT questionnaire. The students also self-reported on their personal-social variables. The descriptive analysis indicated 14% of the students engage in heavy episodic alcohol drinking, with more males being heavy drinkers (28% of the sample) when compared to their female peers (10% of the sample). Being female, attending church at least once a week and being in a non-abusive relationship were associated with lower likelihoods of HEAD. The percentage of women with HEAD increased three-fold from 6% in their first year to 18.4% in the fourth year of study, while that for men increased from 17.2% in the first year to 40% in the second year, then declined to 26.4% in third year before an increase to 34.7% in the fourth year of study. HEAD occurrences were similar across sociodemographic variables. The reasons for females engaging in HEAD more over the period of their university attendance need to be investigated to inform student counselling services.